(Des)conhecimentos, anseios e possibilidades dos estudantes da EJA diante do ensino superior - Fukuhara, Rayana Cavalcante (2024)
The subjects of youth and adult education (EJA) are still distant from higher education. Many factors contribute to this distance, related to social, economic, political, and cultural spheres, among others. EJA students often do not view higher education as a viable option, which further excludes them from an educational formation space. The hypothesis raised is that the lack of knowledge about the higher education universe is a factor to consider in this distancing. Thus, the general objective of this research is to understand and facilitate the expansion of knowledge among high school students in the EJA modality from two public schools in the municipality of São Carlos-SP regarding the universe of higher education. The study involved 42 students from the 2nd and 3rd terms of EJA from both schools. The specific objectives are threefold: I. To identify preliminary knowledge and ignorance about higher education, as well as the ways of entry, access policies, and retention at this level of education; II. To identify what students say about the importance and desire to pursue higher education; III. To analyze students' perceptions on the topic after meetings conducted within the research-intervention context aimed at presenting and discussing information about the higher education universe. This is a qualitative study grounded in the theoretical framework of Paulo Freire (1974; 1986; 1996). The methodological references guiding the intervention are based on the studies of Damiani et al. (2013) and Pereira (2019). A structured questionnaire was used as a research tool to investigate knowledge, ignorance, importance, and desire to pursue higher education. The results showed that 54.7% of participants had no preliminary knowledge about higher education; 64.2% were unaware of quota access; 76.1% did not know the entry stages; 76.9% were unaware of retention programs; and 87.1% declared they had no knowledge about PROUNI and FIES. Among the participants who did not see the importance or desire to enter higher education, all were men aged 18 to 20 years. Regarding the expansion of knowledge about higher education, two meetings were held with each school, organized into five themes: I. What is higher education? II. Public and private institutions. III. Forms of entry. IV. Access policies: Sisu, FIES, PROUNI, and Quotas. V. Student Retention. Of the 38 students who participated in the intervention, 89.4% expressed that the intervention contributed to reflecting on the topic, with 39.4% of participants stating that the activity made them consider the possibility of pursuing higher education. Thus, the study highlights the relevance of addressing the topic within EJA to expand students' knowledge and change their perspective regarding higher education.